An assessment of biogas adoption potential: A pathway to sustainable development in Nala, Rudraprayag, Uttarakhand, India - Sreevidhya C; S. Balamurugan (Sustainable Futures)
India is a major contributor to the development of renewable energy technologies. Firewood and cow dung cakes are the main cooking fuels in rural areas, where biomass makes up 75 % of total energy consumption and pollutes the environment. Decisions to employ clean energy are influenced by intra-household gender disparities because women are largely responsible for cooking and collecting fuel. This study evaluates the use of biogas in line with Sustainable Development Goals (SDG) 7, 5, 13, and 8 while looking at energy consumption, women's labour and carbon emissions in high-altitude community Nala, Rudraprayag, Uttarakhand. The findings show that biogas reduces the amount of time spend by women in firewood gathering by 15 h per month. It also decreases the annual greenhouse gas emissions by 1938.6 kg CO₂e through firewood usage reduction by 5 %. According to these results, biogas is a sustainable energy source that reduces its negative effects on the environment, lowers the work intensity required of women, and advances socioeconomic growth and gender equality. Adoption of biogas addresses important issues with energy use and environmental sustainability and provides a revolutionary route to clean energy in rural, high-altitude low temperature areas.